PENERAPAN DEEP LEARNING BERBANTUAN WORDWALL TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS V SD NEGERI 23 LUBUKLINGGAU - Anggraini, Puput; Fiani, Ani; Rijal, Akmal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the Application of the Deep Learning Learning Model Assisted by Wordwall in Pancasila Education Learning for Fifth Grade Students of SD Negeri 23 Lubuklinggau. This research method is pre-experimental, with the design used is one-group pretest-posttest design. The population in this study were all fifth grade students of SD Negeri 23 Lubuklinggau. Sampling by means of saturated sampling technique, namely in fifth grade of SD Negeri 23 Lubuklinggau totaling 20 students as a sample class. Data collection techniques using multiple choice tests. Data analysis techniques with steps: normality test and Z test. Based on the results of the Z-test analysis with a confidence level obtained α = 0.05 data Z count = 7.88 and Z table = 1.64 then the data shows that the Z count value> z table. The average value of student pretest is 43.55 and the average value of posttest is 85.30, so it can be said that H0 is rejected and Ha is accepted. Thus, it can be concluded that the application of the Wordwall-assisted Deep Learning learning model in Pancasila education learning for fifth-grade students at SD Negeri 23 Lubuklinggau was significantly completed